Seed dormancy and germination requirements in Angelica palustris (Besser) Hofm., a critically endangered plant (Bangladesh Journal of Botany, 2018)
The phenology of Angelica palustris seeds including maturation, germination requirements, and dormancy class, is still unknown. In opposite to the results reported from other species of Angelica, present findings showed that A. palustris produced seeds with embryo underdeveloped (the ratio between the embryo and the whole seed length was between 0.19 and 0.12) and physiologically dormant which corresponded to Morphophysiological Dormancy class. Dormancy breakdown requires a post maturation period (at least 30 days) at 18 - 20ºC for a complete embryo development, and also up to 30 days of cold stratification at 4°C. The best germination indices were obtained when fruit was removed. Germination energy (Ge) was achieved within 19 days after imbibition and was 25.8 + 0.03 and germination per cent (Gp) was achieved within 28 days and was 64.7 + 0.14. Fruit structure (lateral wings with air cavities) and physiology (essential oil production) are adaptations to facilitate seed dispersal and dormancy/germination balance.